2016
DOI: 10.1111/apt.13886
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: recurrence of Crohn's disease after total colectomy with permanent ileostomy

Abstract: Background Subtotal or total colectomy or proctocolectomy with permanent ileostomy (TC-PI) may be a treatment option for medically refractory colonic Crohn's disease (CD). Aim To perform a systematic review and meta-analysis to evaluate the rate, risk factors and outcomes of CD recurrence after TC-PI. Methods In a systematic review ending March 31, 2016, we identified 18 cohort studies (1438 adults) who underwent TC-PI for colonic CD (median follow-up, 7.4 years; interquartile range, 5.3-9.0). We estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 39 publications
(215 reference statements)
0
19
0
1
Order By: Relevance
“…In a recent meta-analysis of 18 cohort studies, the risk of clinical recurrence was 28.0%, with a 5-year and 10-year median cumulative rate of 23.5%. 305 Identification and treatment of early mucosal recurrence may therefore prevent clinical recurrence.…”
Section: Imaging After Surgery [Including Ileo-anal Pouch]mentioning
confidence: 99%
“…In a recent meta-analysis of 18 cohort studies, the risk of clinical recurrence was 28.0%, with a 5-year and 10-year median cumulative rate of 23.5%. 305 Identification and treatment of early mucosal recurrence may therefore prevent clinical recurrence.…”
Section: Imaging After Surgery [Including Ileo-anal Pouch]mentioning
confidence: 99%
“…Surgical removal of the stenosis is a recognized solution, and half of patients require surgery within the first decade of diagnosis. A meta-analysis [33] has reported that small bowel clinical recurrence occurs in approximately 28% of patients after total colectomy with permanent ileostomy for colonic CD. Endoscopic balloon dilation (EBD) is a safe and effective method that can replace small bowel resection in some cases [34].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical removal of the stenosis is a recognized solution, and half of patients require surgery within the first decade of diagnosis. A meta-analysis [33] has reported that small bowel clinical recurrence occurs in approximately 28% of patients after total colectomy with permanent ileostomy for colonic CD. Endoscopic balloon dilation (EBD) is a safe and effective method that can replace small bowel resection in some cases [34].…”
Section: Discussionmentioning
confidence: 99%